Fault tolerant control for DFIG wind turbine controlled by ADRC and optimized by genetic algorithm - Ikram Aissaoui; Noureddine Elmouhi; Ahmed Essadki; Hind Elaimani (Institute of Advanced Engineering and Science, 2023)
This research work deals with the modelling, control and simulation of a wind turbine based on the doubly fed induction generator (DFIG) in the current sensor’s failure event. We present in the first time the model of the wind energy conversion system based on the DFIG and the control by active disturbances rejection control (ADRC) optimized by genetic algorithm. Particular focus is directed towards on a technique for detection, identification, isolation and reconfiguration of current sensor signals after failure. The combination of the two preceding techniques makes it possible to have a fault tolerant control to sensor faults which ensures continuity of service in all circumstances. The robustness of the proposed technique is tested under the MATLAB/Simulink environment.